Comparative Study of Solvent-Assisted Exfoliation of Low Rank Coal for Few-Layer Graphene Production via Multi-Stage Ultrasonication - Gimelliya Saragih; Vivi Purwandari; A. Zukhruf Akbari; Nelson Silitonga; Abdillah Abdillah (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
Low rank coal (LRC), due to its abundance and carbon richness, represents a promising and sustainable precursor for graphene synthesis. This study compares the effects of different solvents CTAB (2%), NaOH (1N), H₂SO₄ (1N), and isopropyl alcohol (IPA)—on the exfoliation efficiency of LRC using a multi-stage ultrasonication approach. The resulting materials were characterized by FTIR, SEM, TEM, and XRD to evaluate their structural, morphological, and chemical properties. The findings reveal that IPA provides the most effective exfoliation, yielding few-layer graphene (FLG) with minimal oxidation and structural distortion. FTIR spectra showed reduced hydroxyl and carbonyl peaks in IPA-treated samples, while SEM and TEM confirmed more open and less-stacked layers. XRD analysis indicated decreased crystallinity and larger interlayer spacing. These results demonstrate that solvent selection plays a critical role in determining exfoliation performance, with IPA emerging as the most efficient and environmentally friendly medium for graphene production from LRC.